Binge Drinking Trajectory and Decision-Making during Late Adolescence: Gender and Developmental Differences - Carbia, Carina; Cadaveira, Fernando; Caamaño-Isorna, Francisco; Rodríguez Holguín, Socorro; Corral, Montserrat (Frontiers in Psychology, 2017)
Objective: Impaired affective decision-making has been consistently related to alcohol dependence. However, less is known about decision-making and binge drinking (BD) in adolescents. The main goal of this longitudinal study was to determine the association between BD and decision-making from late adolescence to early adulthood. A second aim is to assess developmental changes and performance differences in males and females. Method: An initial sample of 155 first-year university students, (76 non-BDs, 40 females; and 79 BDs, 39 females), was followed prospectively over a four-year period. The students were classified as stable non-BDs, stable BDs and ex-BDs according to their scores in item 3 of the AUDIT and the speed of alcohol consumption. Decision-making was assessed by the Iowa Gambling Task (IGT) three times during the study. Dependent variables were net gain and net loss. Results were analysed using generalized linear mixed models. Results: A stable BD pattern was not associated with either disadvantageous decision-making or sensitivity to loss frequency. Performance improved significantly in both genders over the study period, especially in the last blocks of the task. Females showed a higher sensitivity to loss frequency than males. No gender-related differences were observed in gains. Conclusions: Performance in affective decision-making continues to improve in late adolescence, suggesting neuromaturational development in both genders. Females are more sensitive to loss frequency. Stable BD during late adolescence and emerging adulthood is not associated with deficits in decision-making. Poor performance of the IGT may be related to more severe forms of excessive alcohol consumption.